1987
DOI: 10.1007/bf01914568
|View full text |Cite
|
Sign up to set email alerts
|

Comparative thermogravimetric study of chlorinations of hematite and wustite

Abstract: The reactions of hematite and wustite with C12, COC12, CO + C12 and gaseous CC14 were studied by thermogravimetry, X-ray diffraction and computer-assisted thermodynamic calculations. During the chlorination of hematite, only gaseous products were formed. The apparent activation energies were calculated from the isothermal TG curves. The chlorination of wustite involves the formation and transformation of a series of sofid chloride products. FeCl2(s), FeCla(s ) and FeOCl(s) were found as intermediates during ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 5 publications
3
5
0
Order By: Relevance
“…It seems that carbon monoxide has little effect on the chlorination of wüstite at low temperatures during non isothermal treatment. Similar results were reported in other investigations [14], [15] An hematite sample was also subjected to non isothermal treatments under conditions identical to those described above for wüstite. Results obtained for the chlorination of wüstite allow to assume Eqs.…”
Section: Page 6 Of 13 -Textsupporting
confidence: 79%
“…It seems that carbon monoxide has little effect on the chlorination of wüstite at low temperatures during non isothermal treatment. Similar results were reported in other investigations [14], [15] An hematite sample was also subjected to non isothermal treatments under conditions identical to those described above for wüstite. Results obtained for the chlorination of wüstite allow to assume Eqs.…”
Section: Page 6 Of 13 -Textsupporting
confidence: 79%
“…Furthermore, the high E in determined in this study agrees with the high values reported by other authors. [1][2][3][4] For instance, Bertoti et al [1] reported a value of E ap affected by mass transport in the temperature range 873 to 1053 K as great as 188 kJ/mol, which is very similar to the value obtained under the mixed regime (that is, 212 kJ/mol).…”
Section: A Reaction Modelsupporting
confidence: 55%
“…The following chemical equations represent the hematite chlorination: [1][2][3][4][5] Reaction [I] occurs with mass loss due to the formation of iron chloride gaseous. Although it has a DG°positive (viz., DG°5 À0.213 T 1 306 kJ/(mol of Cl 2 )) at the temperatures studied in this paper, it occurs completely under a chlorine flow above 873 K. [1][2][3][4][5] Reaction [II] refers to the equilibrium between FeCl 3 (g) and Fe 2 Cl 6 (g), which is about 50 pct molar at 998 K, [8] decreasing the concentration of Fe 2 Cl 6 (g) as the temperature increases. Hematite powder was placed in a semispherical crucible adopting a loose-pocked bed shape with a high porosity.…”
Section: A Experimental Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers agreed that, whilst using the same chlorinating reagents, the chlorination of hematite starts at higher temperatures than that of wüstite. The final reaction product was found to be FeCl 3 . The values of the apparent activation energy of hematite chlorination varied from about 6 kJ/mol to 190 kJ/mol depending on the chlorinating agent used and on the temperature range explored (Table II).…”
Section: Introductionmentioning
confidence: 98%